Geolocator‐tracking seabird migration and moult reveal large‐scale, temperature‐driven isoscapes in the NE Atlantic. (8th March 2023) - Atkins, Kelly; Bearhop, Stuart; Bodey, Thomas W.; Grecian, W. James; Hamer, Keith; Pereira, Jorge M.; Meinertzhagen, Hannah; Mitchell, Chris; Morgan, Greg; Morgan, Lisa; Newton, Jason; Sherley, Richard B.; et al.
Abstract : Rationale: By combining precision satellite‐tracking with blood sampling, seabirds can be used to validate marine carbon and nitrogen isoscapes, but it is unclear whether a comparable approach using low‐precision light‐level geolocators (GLS) and feather sampling can be similarly effective. Methods: Here we used GLS to identify wintering areas of northern gannets ( Morus bassanus ) and sampled winter grown feathers (confirmed from image analysis of non‐breeding birds) to test for spatial gradients in δ 13 C and δ 15 N in the NE Atlantic. Results: By matching winter‐grown feathers with the non‐breeding location of tracked birds we found latitudinal gradients in δ 13 C and δ 15 N in neritic waters. Moreover, isotopic patterns were best explained by sea surface temperature. Similar isotope gradients were found in fish muscle sampled at local ports. Conclusions: Our study reveals the potential of using seabird GLS and feathers to reconstruct large‐scale isotopic patterns.